2022
DOI: 10.1212/wnl.0000000000013257
|View full text |Cite
|
Sign up to set email alerts
|

Author Response: Early Neurologic Deterioration in Lacunar Stroke: Clinical and Imaging Predictors and Association With Long-term Outcome

Abstract: This collaboration between the American Academy of Neurology (AAN) and the Child Neurology Society (CNS) represents a collection of reprinted cases from the past 15 years from the Neurology Resident & Fellow Section.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
49
2
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 2 publications
12
49
2
2
Order By: Relevance
“…In addition to that, Jiang ( Jiang et al, 2019 ) et al pointed out that the clinical progression of subcortical small infarction was correlated with the history of hypertension, and whether there was a significant correlation needed to be further studied with a large sample. Meanwhile, in our study, aspirin and clopidogrel were the main drugs that patients received during admission, we found no statistical difference between the two groups in combination or single administration of the two drugs, however, Vynckier ( Vynckier et al, 2021 ) et al suggested that dual antiplatelet therapy was associated with reduced risk of clinical progression, the difference between the two results may be attributed to our small sample size.…”
Section: Discussioncontrasting
confidence: 65%
“…In addition to that, Jiang ( Jiang et al, 2019 ) et al pointed out that the clinical progression of subcortical small infarction was correlated with the history of hypertension, and whether there was a significant correlation needed to be further studied with a large sample. Meanwhile, in our study, aspirin and clopidogrel were the main drugs that patients received during admission, we found no statistical difference between the two groups in combination or single administration of the two drugs, however, Vynckier ( Vynckier et al, 2021 ) et al suggested that dual antiplatelet therapy was associated with reduced risk of clinical progression, the difference between the two results may be attributed to our small sample size.…”
Section: Discussioncontrasting
confidence: 65%
“…The relationship between initial NIHSS and END in pontine infarction is unclear. One study showed that higher initial stroke severity was associated with END [17], whereas another study reported that lower initial NIHSS was independently associated with END [6]. In the present study, we found that lower initial NIHSS was related to END.…”
Section: Discussionsupporting
confidence: 51%
“…Although the initial stroke severity, diabetes mellitus, larger infarct volume, initial high blood pressure, and various inflammatory parameters have been proposed, the predictors of END remain uncertain [4]. Recent studies using perfusion imaging have shown that the presence of hypoperfusion in the ischemic area is associated with END [5], which may be related to the subacute increase in the lesion volume [6]. Other studies have shown that arterial tortuosity can induce distortion and stretching of the branching vessels, thereby resulting in hemodynamic instability and hypo-perfused state [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…We hope that more high-quality studies will be designed to study the effects of the infarct site and infarct size on END in the future. Previous BAD-related studies have shown that early intravenous thrombolysis does not prevent the occurrence of END [13,26,27]. Strategies to prevent the occurrence of END are currently an important topic.…”
Section: Discussionmentioning
confidence: 99%